Large-Scale Deployment and Establishment of Wolbachia Into the Aedes aegypti Population in Rio de Janeiro, Brazil - Gesto, João Silveira Moledo; Pinto, Sofia B.; Dias, Fernando Braga Stehling; Peixoto, Julia; Costa, Guilherme; Kutcher, Simon; Montgomery, Jacqui; Green, Benjamin R.; Anders, Katherine L.; Ryan, Peter A.; Simmons, Cameron P.; O’Neill, Scott L.; et al. (Frontiers in Microbiology, 2021)
Traditional methods of vector control have proven insufficient to reduce the alarming incidence of Dengue, Zika and chikungunya in endemic countries. The bacterium symbiont Wolbachia has emerged as an efficient pathogen-blocking and self-dispersing agent that reduces the vectorial potential of Aedes aegypti populations and potentially impairs arboviral disease transmission. In this work, we report the results of a large-scale Wolbachia intervention in Ilha do Governador, Rio de Janeiro, Brazil. wMel-infected adults were released across residential areas between August 2017 and March 2020. Over 131 weeks, including release and post-release phases, we monitored the wMel prevalence in field specimens, and analyzed introgression profiles of two assigned intervention areas, RJ1 and RJ2. Our results revealed that wMel successfully invaded both areas, reaching overall infection rates of 50-70% in RJ1, and 30-60% in RJ2 by the end of the monitoring period. At the neighborhood-level, wMel introgression was heterogeneous in both RJ1 and RJ2, with some profiles sustaining a consistent increase in infection rates and others failing to elicit the same. Correlation analysis revealed a weak overall association between RJ1 and RJ2 (r = 0.2849, P = 0.0236), and an association at a higher degree when comparing different deployment strategies, vehicle or backpack-assisted, within RJ1 (r = 0.4676, P < 0.0001) or RJ2 (r = 0.6263, P < 0.0001). The frequency knockdown resistance (kdr) alleles in wMel-infected specimens from both areas was consistently high over this study. Altogether, these findings corroborate that wMel can be successfully deployed at large-scale as part of vector control intervention strategies, and provide the basis for imminent disease impact studies in Southeastern Brazil.